If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + -3) + 4x = 3(7 + -1x) Reorder the terms: -7(-3 + x) + 4x = 3(7 + -1x) (-3 * -7 + x * -7) + 4x = 3(7 + -1x) (21 + -7x) + 4x = 3(7 + -1x) Combine like terms: -7x + 4x = -3x 21 + -3x = 3(7 + -1x) 21 + -3x = (7 * 3 + -1x * 3) 21 + -3x = (21 + -3x) Add '-21' to each side of the equation. 21 + -21 + -3x = 21 + -21 + -3x Combine like terms: 21 + -21 = 0 0 + -3x = 21 + -21 + -3x -3x = 21 + -21 + -3x Combine like terms: 21 + -21 = 0 -3x = 0 + -3x -3x = -3x Add '3x' to each side of the equation. -3x + 3x = -3x + 3x Combine like terms: -3x + 3x = 0 0 = -3x + 3x Combine like terms: -3x + 3x = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 2x-7+x=5 | | 3(x-4)=7x-20 | | 5(x-10)-6(x-7)=-9(x-8) | | 2(y+4)-5y=28 | | 2*-2-2-23=7 | | 9=15-2n | | -5(x+1)+3+2=6x+4 | | 2(x+20)2=50 | | 12m^2-11m-5=0 | | 2*7-7-23=-2 | | (3x+4)+3x=16 | | -6(4-t)=12tr | | p=2(w+h+l) | | -4(x+6)-12= | | (3x-4)+3x=16 | | 60=6(6-2m) | | (y+x^3y+2x^2)dx+(x+4xy^4+8y^3)dy=0 | | -4(x-6)-12=6 | | 2(x/4-1)=8 | | -4(x-6)-12=12 | | 2000=.05x-99.25 | | 4r^3-1r=0 | | 30=3a | | 1/2(m-6)=12 | | n=.05x-99.25 | | 9c^3-4c=0 | | 2v+5v-13=13 | | 3x+(3x+4)=16 | | 60t^4v+78t^3v-180t^2v=0 | | 9v^3-16v=0 | | 15t-22=13-15t | | 3x+(3x-4)=16 |